Strategija regionalnega razvoja v Sloveniji - Piry, Ivo (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2003)
The article discusses the role of planning in the field of regional development, as it is defined with the Strategy of Regional Development of Slovenia. The importance of the strategy is shown by its elements, vision, principles and quantified targets, and with institutional framework which teritorial dimension is seen in the division of Slovenia into twelve statistical regions. National Development Plan 2002-2006 is presented as operationalisation of the strategy.
Keywords: ekonomski razvoj; gospodarske panoge; podjetništvo; razvojna strategija; razvojni programi; regije; regionalni razvoj; Slovenia; Slovenija; sustainable development; trajnostni razvoj